Cultivating Ecological Sensitivity: How Ecolinguistics Enhances Descriptive Writing Skills at UPMI - Hariati, Puji (English Teaching and Linguistics Journal (ETLiJ), 2025)
This study aimed to explore how the integration of ecolinguistic principles in teaching descriptive writing could enhance students’ writing skills and ecological sensitivity. The research involved 30 third semester students of the English education program at University of Pembinaan Masyarakat Indonesia (UPMI). Using a qualitative descriptive approach with elements of classroom action research. Data were collected through pre-test and post test, classroom observation, questionnaires, and interview. The findings revealed significant improvements in students’ paragraph structure, ecological vocabulary, and empathetic expression towards environmental issues. A total of 80% of students demonstrated improved paragraph unity and coherence, 70% used environmentally themed vocabulary and metaphors, and 65% explicitly expressed ecological values in their writing. These results indicate that the ecolinguistic approach not only enhances the quality of descriptive writing but also cultivates environmental awareness through language. The study recommends integrating ecolinguistic content into language curricula to support sustainable education.